Sales training: A state of the art and contemporary review - Vijay Lakshmi Singh; Ajay K. Manrai; Lalita A. Manrai (Journal of Economics, Finance and Administrative Science, 2015)
Organizations of today face numerous challenges, and training their sales force is definitely high on its agenda. This paper endeavors to contribute to the sales training field by providing a comprehensive state-of-the art and contemporary review through the study of publications in sales training research in the last 30 years (1985-2014). The specific objectives of the review are to study the chronological trends and structural distribution of sales training research in terms of the research type, research focus, methods, research themes and other issues such as methodology, analytical techniques, geographical region etc. Findings of 56 articles on sales training research published in the last three decades are analyzed and directions for future research are identified. – – Las organizaciones actuales se enfrentan a numerosos retos, siendo prioritaria en su agenda la formación de su fuerza de ventas. El presente documento pretende contribuir en este campo, mediante la aportación de una revisión amplia, vanguardista y contemporánea del estudio de las publicaciones sobre la investigación de la formación en ventas durante los últimos 30 a\~nos (1985-2014). Los objetivos específicos de la revisión son el estudio de las tendencias cronológicas y la distribución estructural de la investigación de la formación en ventas, en términos de tipo, objetivo y temas de la investigación, así como otras cuestiones tales como la metodología, las técnicas analíticas, la región geográfica, etc. Se analizan los hallazgos de 56 artículos sobre investigación de la formación en ventas, publicados durante los últimos treinta a\~nos, y se identifican las orientaciones de la investigación futura.
Keywords: E31; 330; Sales; Training; Assessment; Implementation; Evaluation; Performance; Ventas; Formación; Valoración; Implementación; Evaluación; Desempe\~no